REPRESENTASI DESA DALAM FILM-TARI â€œDONGENG DARI DIRAHâ€ Analisis Semiotika Barthesian - Hudoyo, Sapto (Seni Media Rekam ISI Surakarta, 2011)
Film is a collaborative work that combines multiple art forms. Every form of art donatesrespective roles and supports each other. Film is created as a means of communicationvia meaningful visual language and affirmed-narrative. A film raises aesthetic values andmeaning by offering interpretation from its audience. The story telling throughchoreography on the step of post-production (editing) will bring new meaning, it makesa dance film more superior than the performances of casual dance. Dance has becomea means of creating a depth of meaning on purpose to be conveyed. By using a semiotictheory, a â€œSocerres From Dirahâ€ dance film which has rural setting can be perceivedthrough culture and religion of rural communities. Of the signs systems (signifier/expression and signified/contents), it has obtained connotative meaning of the effort,praying and expression of excitement for all the work done by rural communities inmaking a living for his family.